Sequence diagrams: an aid for digital ecosystem developers - McMeekin, David; Hadzic, Maja; Chang, Elizabeth (IEEE, 2009)
Creating, modifying and/or maintaining a software system is a time consuming and complex process. The digital ecosystem is a new concept introduced into the computer science and information systems world. New and already existing systems need to be integrated into these wider digital ecosystems. Here, it is crucial for the developer to understand the systems that need to be integrated to ensure that the modifications are effective and do not introduce new defects into the system. Developers need to be able to effectively model such systems to assist them in their system understanding, enabling them to create, modify and evolvethe system into the associated digital ecosystems. This paper proposes sequence diagrams be used to represent and model the collaborative nature of digital species within digital ecosystems to assist developer understanding and comprehension of these systems. An illustration from the health domain, specifically, anelectronic health records application is given. Also, a conjecture is also made within the paper that some software systems, in and of themselves, reflect and resemble the attributes and characteristics of a digital ecosystem.